Strengthening Citizen Political Education to Muhammadiyah Youth - Sulton Sulton; Ardhana Januar Mahardhani; Sunarto Sunarto (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2021)
Islamic education as an agent of social change must always be dynamic in responding to all the problems that exist in society. The existence of youth organizations such as Pemuda Muhammadiyah must be able to provide new views and be proactive in carrying out activities including civic democracy. The method used is qualitative, primary data obtained from in-depth interviews with 8 purposively selected informants, especially those who are actively involved in running the organization. Observation of documents related to the implementation of organizational programs will produce secondary. Data analysis was carried out simultaneously during the data mining process using the interactive analysis model offered by Huberman and Miles. The results obtained are that Muhammadiyah Youth needs space in the context of self-existence, namely through strengthening the politics of recognition and redistribution. The research conclusions are that Muhammadiyah Youth to be able to build balanced power relations through their activists and institutionally can begin with the educational process and organizational learning in organizations outside of school, namely the Muhammadiyah Student Association and the Muhammadiyah Student Association.